2016
DOI: 10.14504/ajr.3.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Stress Relief Effect by Use of Aroma-Therapeutic Textiles

Abstract: The efficacy of aroma-therapeutic textiles was quantified by gauging the psychophysiological responses of twenty female subjects exposed to treated as well as untreated textile specimens. In congruence with previous studies, statistical analysis of the psychophysiological responses showed stress relief in subjects after exposure to the essential oils. Aroma-therapeutic textiles in this study were developed by finishing 100% cotton fabric with β-cyclodextrin and one of two essential oils using the sol-gel metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In summary, helichrysum oil possesses diverse properties such as anti-allergic, antibacterial and antiaging effects, making it widely used in the cosmetic industry. However, in order to transfer essential oils to textile materials and ensure their long-lasting effectiveness, different methods of transfer are necessary (Ghayempour and Montazer, 2016; Mehta and MacGillivray, 2016; Ghosh and Chipot, 2015). It has been observed that helichrysum oil helps heal conditions such as wounds, cuts and burns on the skin due to its strong anti-inflammatory and antiseptic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, helichrysum oil possesses diverse properties such as anti-allergic, antibacterial and antiaging effects, making it widely used in the cosmetic industry. However, in order to transfer essential oils to textile materials and ensure their long-lasting effectiveness, different methods of transfer are necessary (Ghayempour and Montazer, 2016; Mehta and MacGillivray, 2016; Ghosh and Chipot, 2015). It has been observed that helichrysum oil helps heal conditions such as wounds, cuts and burns on the skin due to its strong anti-inflammatory and antiseptic effects.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the aforementioned oil possesses various properties such as anti-allergic, antibacterial and antiaging effects, making it widely used in the cosmetic industry. However, in order to transfer the essential oils to textile materials and ensure their long-lasting effectiveness, different methods need to be employed (Ghayempour and Montazer, 2016; Mehta and MacGillivray, 2016; Ghosh and Chipot, 2015; Kunc et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%